Implementation of Home Care Services by Community Health Centers (Puskesmas) in Makassar City, Indonesia - Kusrini Semarwati Kadar; Fitrah Ardillah; Arnis Puspitha; Erfina Erfina (Jurnal Keperawatan Indonesia, 2022)
Home care services by health professionals, such as doctors, nurses, and other health care professionals, target to provide health care services, including health education, physical examination, or other treatments such as physical therapy or medication. This study aimed to evaluate the implementation of home care (nursing care and home care services) in Makassar City in accordance with government guidelines. A qualitative descriptive study was conducted by interviewing nurses (15 participants) from several community health centers (Puskesmas) in Makassar City, Indonesia who have implemented a home care program for at least a year. Four main themes had emerged, namely, management of home care services, nurses’ roles in home care services, perceived barriers, and community benefits. Despite some barriers, the home care programs delivered by health care professionals including nurses in Puskesmas in Makassar City have been well implemented in accordance with the guidelines. On the basis of the obstacles faced by the nurses, one recommendation is for the government to provide specific guidelines on the types of patients to be included in these services. The government also needs to ensure that the community knows the types of patients’ condition who can avail these services.Abstrak Implementasi Pelayanan Perawatan di Rumah (Home Care) oleh Puskesmas di Kota Makassar, Indonesia. Pelayanan perawatan di rumah (home care) oleh petugas kesehatan seperti dokter, perawat, dan petugas kesehatan lainnya bertujuan untuk memberikan pelayanan kesehatan meliputi pendidikan kesehatan, pengkajian fisik, atau memberikan terapi fisik ataupun pengobatan. Penelitian ini bertujuan untuk mengevaluasi kesesuaian antara implementasi pelaksanaan pelayanan home care di kota Makassar dengan petunjuk teknis pelaksanaan home care dari pemerintah. Penelitian ini adalah penelitian deskriptif kualitatif dengan melakukan wawancara mendalam kepada 15 orang perawat dari beberapa Puskesmas di kota Makassar, Indonesia, yang terlibat dalam kegiatan pelayanan home care minimal selama satu tahun. Terdapat empat tema utama yang ditemukan dalam penelitian ini antara lain, pengelolaan home care, peran perawat dalam pelaksanaan home care, hambatan dalam pelaksanaan home care, dan manfaat dari pelaksanaan home care di kota Makassar. Secara umum, pelaksanaan kegiatan home care sudah dilaksanakan sesuai petunjuk teknis dengan baik oleh perawat di Puskesmas kota Makassar walaupun masih ada beberapa hambatan dalam pelaksanaan kegiatan ini. Pemerintah diharapkan membuat petunjuk pelaksanaan (SOP) yang lebih jelas terkait pelaksanaan kegiatan ini atau melakukan pembaharuan regulasi terkait program ini. Kata Kunci: home care, peran perawat, puskesmas